Assessing the effectiveness of integrated non-communicable disease and antiretroviral adherence clubs in Cape Town, South Africa - Gausi, Blessings (Department of Public Health and Family Medicine, 2020)
The growing burden of HIV and non- communicable disease (NCD) syndemic in Sub Saharan Africa, has necessitated introduction of integrated models of care in order to leverage existing HIV care infrastructure for NCDs. However, there is paucity of literature on long term treatment outcomes for multimorbid patients attending integrated care. We describe long term treatment outcomes among multimorbid patients who attended integrated ART and NCD clubs (IC), a novel model of care piloted in 2014 by the Western Cape Government in South Africa. We followed up multimorbid patients for 12 months, who enrolled for IC at Matthew Goniwe and Town II clinics before September 2016. Median adherence proportions, HIV viral suppression and retention rates were calculated at 12 months before and after IC enrolment. Rates for achieving targets for blood pressure and glycosylated haemoglobin were determined at 12 months prior, at IC enrolment and at 12 months post IC enrolment. We describe demographic and clinical variables among all patients at IC enrolment and used multivariable logistic regression to evaluate for predictors of NCD control 12 months post IC enrolment. As of 31 August 2017, 247 patients in total had been enrolled into IC for at least 12 months. Of these, 221 (89.5%) had hypertension, 4 (1.6%) had diabetes mellitus and 22 (8.9%) had both in addition to HIV. Adherence was maintained before and after IC enrolment with median adherence proportions of 1 (IQR 1-1) and 1 (IQR 1-1) respectively. HIV viral suppression rates were 98.6%, 99.5% and 99.4% at the three time points respectively. Retention in care was high with 6.9% lost to follow up at 12 months post IC enrolment. Optimal blood pressure control was achieved in 43.1%, 58.9% and 49.4% of participants whereas optimal glycaemic control was achieved in 47.4%, 87.5% and 53.3% of diabetic participants at the three time points respectively. Multivariable logistic analyses showed no independent variables significantly associated with NCD control. Multi-morbid people living with HIV achieved high levels of HIV control in integrated HIV and NCD clubs. However, intensified interventions are needed to maintain NCD control in the long term.